What Causes the Postmonsoon 18O Depletion Over Bay of Bengal Head and Beyond?. Issue 4 (20th February 2020) - Cai, Zhongyin; Tian, Lide
Abstract: Modern observations from Bay of Bengal (BOB) head have shown that precipitation δ 18 O value reaches the lowest stage during late postmonsoon when the summer monsoon has weakened or retreated, complicating the traditional interpretation of low δ 18 O value as strong monsoon. We show that this postmonsoon 18 O depletion phenomenon exists from BOB periphery to the southeast and south Tibetan Plateau. Accumulative precipitation along back‐trajectory still explains daily precipitation δ 18 O variability during both the monsoon and nonmonsoon, thus indicating that longer‐term weighted‐mean δ 18 O is biased toward synoptic conditions during precipitation events. Further, we propose that transport of moisture from the east (west) of the India‐Burma Trough leads to depleted (enriched) 18 O during the postmonsoon (premonsoon). Our results reconcile the apparent contradiction but beg the consideration of potential bias and influence of different precipitation regimes in paleo archives. Plain Language Summary: Oxygen isotope signal (δ 18 O) retrieved from various geological archives, for example, speleothems, reflects paleo‐precipitation δ 18 O variability and has been used as a proxy of monsoon intensity in South Asia based on the generally negative correlation between δ 18 O and rainfall amount. However, precipitation δ 18 O over the Bay of Bengal (BOB) head shows the lowest values during September–October where rainfall peaks during June–August, complicating the interpretation of δ 18 O records from paleo archives. We show that daily precipitation δ 18 O variability still correlates with accumulative rainfall along moisture transport paths. While averaged toward monthly means, precipitation δ 18 O shows a more robust relationship with rainfall intensity rather than the classical monthly total rainfall, indicating that longer‐term mean δ 18 O is biased toward precipitation events. We further propose that moisture transport pathways from the east of the trough embedded in the southern branch westerlies after the summer monsoon lead to stronger isotopic distillation and thus more depleted precipitation 18 O, and the opposite before the monsoon. Key Points: Precipitation 18 O shows a postmonsoon depletion over Bay of Bengal head, and this phenomenon extends to a large region in South Asia Accumulative precipitation along back‐trajectory well explains daily and monthly precipitation δ 18 O variabilities Transport of moisture from the front of the India‐Burma Trough leads to the postmonsoon 18 O depletion and opposite for the premonsoon